Characteristic plume morphologies of atmospheric Ar and He plasma jets excited by a pulsed microwave hairpin resonator *Project supported by the National Natural Science Foundation of China (Grant Nos. 11575003 and 51607003). (May 2018) - Chen 陈, Zhao-Quan 兆权; Zhou 周, Ben-Kuan 本宽; Zhang 张, Huang 煌; Hong 洪, Ling-Li 伶俐; Zou 邹, Chang-Lin 长林; Li 李, Ping 平; Zhao 赵, Wei-Dong 卫东; Liu 刘, Xiao-Dong 晓东; Stepanova, Olga; Kudryavtsev, A A
Abstract : Different discharge morphologies in atmospheric Ar and He plasmas are excited by using a pulsed microwave hairpin resonator. Ar plasmas form an arched plasma plume at the opened end of the hairpin, whereas He plumes generate only a contracted plasmas in between both tips of metal electrodes. Despite this different point, their discharge processes have three similar characteristics: (i) the ionization occurs at the main electrode firstly and then develops to the slave electrode, (ii) during the shrinking stage the middle domain of the discharge channels disappears at last, and (iii) even at zero power input (in between pulses) a weak light region always exists in the discharge channels. Both experimental results and electromagnetic simulations suggest that the discharge is resonantly excited by the local enhanced electric fields. In addition, Ar ionization and excitation energies are lower than those of He, the effect of Ar gas flow is far greater than that of He gas, and the contribution of accelerated electrons only locates at the domain with the strongest electric fields. These reasons could be used to interpret the different characteristic plume morphologies of the proposed atmospheric Ar and He plasmas.